2014
DOI: 10.1098/rstb.2013.0595
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial cradle in the life of the synapse

Abstract: Astroglial perisynaptic sheath covers the majority of synapses in the central nervous system. This glial coverage evolved as a part of the synaptic structure in which elements directly responsible for neurotransmission (exocytotic machinery and appropriate receptors) concentrate in neuronal membranes, whereas multiple molecules imperative for homeostatic maintenance of the synapse (transporters for neurotransmitters, ions, amino acids, etc.) are shifted to glial membranes that have substantially larger surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
196
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 94 publications
(131 reference statements)
2
196
0
Order By: Relevance
“…Atrophy of astroglial perisynaptic processes, which foster and maintain synaptic transmission (as embellished by the concept of the astroglial cradle - [109]) can be an important (if not the leading) mechanism of synaptic weakening and synaptic loss that signals the beginning of AD pathology [110]. General decrease in the astroglial homeostatic reserve reduces neuroprotection and may be detrimental for the neuro-vascular unit and may affect the glial ability to metabolically support neuronal networks.…”
Section: Astroglia In Admentioning
confidence: 99%
“…Atrophy of astroglial perisynaptic processes, which foster and maintain synaptic transmission (as embellished by the concept of the astroglial cradle - [109]) can be an important (if not the leading) mechanism of synaptic weakening and synaptic loss that signals the beginning of AD pathology [110]. General decrease in the astroglial homeostatic reserve reduces neuroprotection and may be detrimental for the neuro-vascular unit and may affect the glial ability to metabolically support neuronal networks.…”
Section: Astroglia In Admentioning
confidence: 99%
“…Some argued that glia existed merely to fill the otherwise empty spaces and provide a structural matrix, within which neurones are embedded [9], whereas some, however, went much further and assigned glia fundamental homeostatic functions [25] , whilst still others, most notably Carl Ludwig Schleich and Santiago Ramón y Cajal, suggested that glial cells control local blood flow, initiate sleep, and regulate information transfer in neuronal networks [8,14,26]. It is now apparent that astrocytes fulfil all of these operations and more, including the most fundamental neuronal attribute of synaptogenesis [27][28][29][30]. Similarly, the fundamental role of neuroglia in neurological diseases was highlighted by the most prominent neuropathologists, such as Franz Nissl, Carl Frommann, Ludwig Merzbacher, Alois Alzheimer, and Nicolas Achucarro [13,[31][32][33][34].…”
mentioning
confidence: 99%
“…They subdivide progressively to form finer and finer processes of up to 100.000 per astrocyte. Most of these processes interact with synapses, termed perisynaptic astrocytic processes (PSAPs) [19]. Fewer processes contact vessels, called perivascular astrocytic processes (PVAPs) [20].…”
Section: Perisynaptic Astrocytic Processesmentioning
confidence: 99%